Answer:
108
Step-by-step explanation:
do u guys stay on this and text on this
Answer:
x=3
Step-by-step explanation:
lets take x as the number
so
6(x-3)=x-3
since it says "6 times" we know that we will have to multiply the difference by 6 and it says the difference of a number and 3 is equal to 3 less than the number so we know that we are subtracting 3 from x
6x-18=x-3
6x-x=18-3
5x=15
x=3
Answer:
C(N(h)) = 1400h +530
Step-by-step explanation:
x = N(h), so substitute in the expression for N(h) to get x
C(N(h)) = 35(40h) + 530
=> 1400h + 530
now pray for my lazy brain to check work it is correct
Answer:
24
Step-by-step explanation:
So for you’r question its definitely B